ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI KUALITAS SUMBER DAYA MANUSIA DI TANJUNGPINANG TAHUN 2023 - Likuwatan, Paris; SUTRAJAT; Muhammad Ayyub Harahap (Jurnal Dialektika Politik, 2024)
This research analyzes the factors that influence the quality of human resources in Tanjungpinang in 2023. The quality of human resources is an important aspect in the development of a region, which includes abilities, skills, knowledge, as well as individual attitudes and work ethics. This study uses a quantitative approach with survey methods to collect data from various sectors in Tanjungpinang, including the education, health, economic and social sectors. Data was collected through questionnaires distributed to a representative sample of the Tanjungpinang population. Data analysis was carried out using multiple regression techniques to identify the main factors that have a significant influence on the quality of human resources. The research results show that educational factors have the most dominant influence on the quality of human resources in Tanjungpinang. Apart from that, health factors also play an important role, where access to health facilities and the general level of public health contribute to the quality of human resources. Economic factors, including per capita income and unemployment rates, were also found to have a significant influence. Meanwhile, social factors such as the family environment and participation in community activities also have a positive impact on improving the quality of human resources. These findings underline the importance of investment in the education and health sectors as an effort to improve the quality of human resources in Tanjungpinang. Regional governments are advised to improve access and quality of education and health services, in addition to encouraging inclusive and sustainable economic growth. Active community participation in social activities also needs to be encouraged to create an environment that supports the development of quality human resources. It is hoped that this research can become the basis for formulating more effective policies in improving the quality of human resources in Tanjungpinang.